Climatic features of distribution of precipitation on the territory of South and Southeast of Kazakhstan in warm period of year (Journal of Geography and Environmental Management, 2019)
The analysis of data about quantity of deposits during the period from 1970 to 2004 for the warm period iscarried out. The catalogue of the months with deficiency, normal quantity and surplus of deposits is made. The analysisof the time course of atmospheric precipitation which visually reflects changes of deposits on the territory consideredhas shown that the tendency of reduction of deposits is marked.